Refining of a low-grade molybdenite concentrate - Kumar M.; Mankhand T.R.; Murthy D.S.R.; Mukhopadhyay R.; Prasad P.M. (My University, 2025)
This study aims to refine an indigenous off-grade molybdenite [41.5% Mo] to one of high-grade MoS2 for industrial applications. Investigations were carried out on the removal of the oxide/silicate gangue and the base metal sulphide associations by their selective dissolution in two acids, namely, HCl or HF deployed singly, sequentially or in the mixed mode. Under optimum conditions practically all the oxide and silicate gangue and 90% of the metallic impurities were removed. Starting from the low-grade molybdenite concentrate a refined molybdenite (97.8% MoS2) was made whose composition compares well with that of a technical-grade MoS2 of the Climax Molybdenum Company. © 2006 Elsevier B.V. All rights reserved.